2013
DOI: 10.1111/ijn.12034
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting health status in patients with chronic obstructive pulmonary disease

Abstract: The aim of this study is to determine the correlation between the quality of life (QOL) and subjective dyspnoea, subjective fatigue, sleep quality, and the forced expiratory volume in first second (FEV(1)) % predicted value and collective contribution of these variables on QOL. The study was conducted with 102 patients. Pulmonary function tests (FEV(1) % predicted value, FEV(1) /forced vital capacity), subjective dyspnoea, subjective fatigue, sleep quality were assessed. There were negative correlations betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
3
7
1
Order By: Relevance
“…This result is near the results of Akinci and Yildrin (2013) [33] who found that the mean years of disease duration for their sample was 9.1±8.5 years.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This result is near the results of Akinci and Yildrin (2013) [33] who found that the mean years of disease duration for their sample was 9.1±8.5 years.…”
Section: Discussionsupporting
confidence: 81%
“…These percentages are less than the percentage of Salah et al, (2013) and Akinci and Yildrin (2013) who stated that most of their sample was male [30,33]. This may be due to the lower sample size of the current study in relation to their sample size.…”
Section: Discussioncontrasting
confidence: 66%
“…Another factor for caregiver needs of patients with COPD is reduction in physical activity resulting from increased severity of the disease (9). Therefore, the patients have difficulty in fulfilling their daily life activities (8,(18)(19)(20). In a study by T€ urk and € Ust€ un, with progression of COPD, advanced age and chronic diseases, the patients were found to become more dependent.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that baseline characteristics such as male gender, older age, lower level of education, lower body weight, more respiratory symptoms, severe airflow limitation, and symptoms of anxiety and depression are related to deterioration in generic and disease‐specific health status in patients with COPD . In addition, frequent exacerbations during follow‐up have been shown to be related to deterioration in disease‐specific health status .…”
Section: Introductionmentioning
confidence: 99%
“…6 Previous studies have shown that baseline characteristics such as male gender, older age, lower level of education, lower body weight, more respiratory symptoms, severe airflow limitation, and symptoms of anxiety and depression are related to deterioration in generic and disease-specific health status in patients with COPD. [7][8][9][10][11][12] In addition, frequent exacerbations during follow-up have been shown to be related to deterioration in diseasespecific health status. 13 Previous authors suggested that the rate of decline in forced expiratory volume in the first second (FEV 1 ) is related to the rate of increase in St George's Respiratory Questionnaire (SGRQ) score.…”
Section: Introductionmentioning
confidence: 99%